Length–weight relationships of 22 fish species from the East China Sea. (8th December 2014) - Yagi, M.; Yamada, M.; Shimoda, M.; Uchida, J.; Kinoshita, T.; Shimizu, K.; Yamawaki, N.; Aoshima, T.; Morii, Y.; Kanehara, H.
Summary: Estimated length–weight relationships are presented for 22 commercially important marine fish species representing nine families, found in the East China Sea. A total of 2776 specimens were caught by otter trawl on the continental shelf in the East China Sea between 2009 and 2013. Information pertaining to length–weight relationships should lead to a better understanding of fish communities in the East China Sea.